UNDERWATER OBJECT SHAPE DETECTION BASED ON TONAL DISTRIBUTION AND EDGE DETECTION USING DIGITAL IMAGE PROCESSING - Suryowinoto, Andy; Herlambang, Teguh; Baital, Muhammad Sawal; Tomasouw, Berny Pebo (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
Underwater exploration activities always have their own charm, many exotic objects that exist in underwater ecosystems have not been mapped properly, due to the lack of related databases of the shapes and names of these underwater objects. Another factor that affects the visibility of objects related to the quantity of light intensity that enters under water, also not as much above the surface of the abundant water, especially during the day. This also hinders the process of documenting underwater objects. The main purpose of this study was to obtain the shape of underwater objects for several conditions of light intensity under water using a low cost digital image sensor camera. The method used in this research is to combine tonal distributions with object edge detection in digital image processing. The test results show that object detection tests in clear and turbid water can detect objects even though they are using a low-cost and low-resolution camera, but with the help of adequate lighting it can be done. From that it can be concluded that the detection of underwater objects is successful.